A new method for the determination of cadmium at ultratrace levels using slotted quartz tube-flame atomic absorption spectrometry after preconcentration with stearic acid coated magnetite nanoparticles. Issue 12 (15th November 2017) - Akkaya, Erhan; Aylin Kasa, Nursu; Çetin, Gülten; Bakirdere, Sezgin
Abstract : A combination of slotted quartz tube attached flame atomic absorption spectrometry (SQT-FAAS) and stearic acid coated magnetite nanoparticle based solid phase microextraction (SPME-MNP) was used for the determination of ultratrace amounts of cadmium. Abstract : A combination of slotted quartz tube attached flame atomic absorption spectrometry (SQT-FAAS) and stearic acid coated magnetite nanoparticle based solid phase microextraction (SPME-MNP) was used for the determination of ultratrace amounts of cadmium. Coated magnetite nanoparticles were used for the extraction of cadmium from aqueous samples by providing a large surface area with the help of their surfactant properties. The separation of the extracted cadmium from the aqueous phase was facilitated by the application of an external magnetic field. Several experimental variables such as the mixing type, duration of mixing, pH of buffer solution and amount of eluent were optimized in order to enhance the extraction efficiency for cadmium. Under the optimum experimental and instrumental conditions, 0.11 μg L −1 limit of detection (LOD) and 0.36 μg L −1 limit of quantification (LOQ) were obtained. Recovery tests were carried out to investigate the effect of a sample matrix on the developed method and the percent recoveries obtained were between 97 and 105% for spiked lake water and urine samples. A standard reference material of tomato leaves (NIST 1573a) was also analysed to validate the accuracy of the developed method and the experimental result agreed with the certified value. Low percent relative standard deviation values also indicated high precision.